Analysis of fatigue development during elite male handball matches - Póvoas, S. C. A.; Ascensão, A. A. M. R.; Magalhaes, J.; Seabra, A. F. T.; Krustrup, P.; Soares, J. M. C.; Rebelo, A. N. C. (The Journal of Strength and Conditioning Research, 2014)
This study aimed at describing the physiological demands and fatigue development during elite male handball matches. Our hypothesis was that players perform multiple high-intensity activities during periods of the game and develop temporary and end-match neuromuscular fatigue. Time-motion analyses and heart rate (HR) recordings were performed in 40 players during 12 competitive matches. Blood samples were collected, and sprint, jump, and intermittent exercise performance (Yo-Yo Intermittent Endurance level 2 test [YYIE2]) was assessed for 18 players at baseline conditions and after 2 competitive matches, and additional blood sampling and testing were performed for 12 of these players during a friendly match. The time spent with high-intensity running (4.4 ± 2.0 to 3.1 ± 1.7%), the frequency of demanding actions (61 ± 5 to 54 ± 6), and the time with HR above 80% HRmax (62 ± 21 to 41 ± 17%) were lowered from the first to the second half. Average blood lactate during the match was 3.6 ± 2.1 (1.3-8.6) mM. Plasma free fatty acids (FFA), glycerol, glucose, and uric acid increased (p < 0.05) during the first half and plasma FFA and glycerol increased further (p < 0.05) during the second half. After an intense period in the second half, sprint performance was decreased by 3.9 ± 4.9%. After the match, YYIE2 (33.4 ± 8.7%), vertical jump (7.4 ± 6.5%), and 20-m sprint performance (1.6 ± 2.6%) was lower (p ? 0.05) than at baseline. This study showed that the intensity is high in certain periods during elite male handball games and that physical performance is impaired both temporarily during and toward the end of games confirming our hypothesis. These findings enables physical trainers and coaches to plan and design proper game-specific training exercises aiming at delaying both temporary and end-game fatigue and strengthen the physiological rationale for the need for substitutions in various stages of match-play.